2020
DOI: 10.1021/acsaem.9b02314
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study into Interface Structure and Band Alignment of the Cu2Zn1–xCdxSnS4 Heterointerface for Photovoltaic Applications

Abstract: To improve the constraints of kesterite Cu 2 ZnSnS 4 (CZTS) solar cell, such as undesirable band alignment at p–n interfaces, bandgap tuning, and fast carrier recombination, cadmium (Cd) is introduced into CZTS nanocrystals forming Cu 2 Zn 1– x Cd x SnS 4 through cost-effective solution-based method without postannealing or sulfurization treatments. A syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…4 The lower efficiency of CZTSSe compared to the chalcogenide Cu(In,Ga)(S,Se) 2 (CIGS) counterparts (420% efficiency) has been attributed to several factors, including but not limited to, large open-circuit voltage (V oc ) deficits, [5][6][7] high-defect states, 8 co-existence of secondary phases, 9,10 short carrier lifetime, 11 and unfavorable band offset and alignment at the CZTSSe/buffer interface. 12,13 In addition to these issues, the kesterite based photovoltaic devices suffer from severe band tailing, which particularly reduces the open circuit voltage (V oc ) of solar cells. 14 Rey et al reported the origin of band-tails in kesterite materials and showed that the large band tailing causes voltage losses that limit the efficiency of kesterite-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…4 The lower efficiency of CZTSSe compared to the chalcogenide Cu(In,Ga)(S,Se) 2 (CIGS) counterparts (420% efficiency) has been attributed to several factors, including but not limited to, large open-circuit voltage (V oc ) deficits, [5][6][7] high-defect states, 8 co-existence of secondary phases, 9,10 short carrier lifetime, 11 and unfavorable band offset and alignment at the CZTSSe/buffer interface. 12,13 In addition to these issues, the kesterite based photovoltaic devices suffer from severe band tailing, which particularly reduces the open circuit voltage (V oc ) of solar cells. 14 Rey et al reported the origin of band-tails in kesterite materials and showed that the large band tailing causes voltage losses that limit the efficiency of kesterite-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that CdS would be a more appropriate choice of partner material for CSTS from an electronic point of view, because of the smaller CBO between CSTS and CdS, which is also often the first successful choice as the n-type partner material for CIGS 66 , CdTe 67 , and CZTS 68 , 69 absorbers. The slightly larger CBO at the CSTS/CdS interface compared to that of the CZTS/CdS interface (0.21 eV) 68 , 69 , indicates that interface and band offset engineering is required to lower the barrier height at the CSTS/CdS interface and promote efficient charge carrier separation. As was demonstrated to improve the performance of SnS solar cells 70 , 71 , a contact metal with lower work function may be needed at the opposite sides of the junction for CSTS.…”
Section: Resultsmentioning
confidence: 97%
“…The sign of γ interface signifies whether the interface is more (negative value) or less (positive value) stable than the respective bulk materials in isolation. This method has been used to provide significant insights into the stability of the interfaces of PV materials, for example CZTS/CdS (Rondiya et al, 2019;Rondiya et al, 2020), CCTS/CdS (Rondiya et al, 2020) and TiO 2 /hybrid perovskites. (Mosconi et al, 2014).…”
Section: Atomistic Modelling Of Photovoltaic Interfacesmentioning
confidence: 99%